Triptolide Modulates the Expression of Inflammation-Associated lncRNA-PACER and lincRNA-p21 in Mycobacterium tuberculosis–Infected Monocyte-Derived Macrophages - Tamgue, Ousman; Chia, Julius Ebua; Brombacher, Frank (Frontiers in Pharmacology, 2021)
Triptolide is a diterpene triepoxide which performs its biological activities via mechanisms including induction of apoptosis, targeting of pro-inflammatory cytokines and reshaping of the epigenetic landscape of target cells. However, the targeting of long non-coding RNAs (lncRNAs) by Triptolide, has not yet been investigated, despite their emerging roles as key epigenetic regulators of inflammation and immune cells function during Mycobacterium tuberculosis (Mtb) infection. Hence, we investigated whether Triptolide targets inflammation-associated lncRNA-PACER and lincRNA-p21 and how this targeting associates with Mtb killing within Monocyte-Derived Macrophages (MDMs). Using RT-qPCR we found that Triptolide induced the expression of lincRNA-p21 but inhibited the expression of lncRNA-PACER in resting MDMs in a dose- and time-dependent manner. Moreover, Mtb-infection induced the expression of lincRNA-p21 and lncRNA-PACER, and exposure to Triptolide before or after Mtb-infection led to further increase of Mtb-induced expression of these lncRNAs in MDMs. We further found that, contrary to lncRNA-PACER, Triptolide time- and dose-dependently upregulated Ptgs-2, which is a proximal gene regulated by lncRNA-PACER. Also, low concentration Triptolide inhibited the expression of the cytokine IL-6, a known target of lincRNA-p21. Mtb-infection induced the expression of IL-6 and Ptgs-2 and Triptolide-treatment further increased IL-6 but decreased Ptgs-2 expression in Mtb-infected MDMs. The inverse relation between the expression of these lncRNAs and their target genes is concordant with the conception that these lncRNAs mediate at least partially the cytotoxic and/or anti-inflammatory activities of Triptolide in both resting and activated MDMs. Using CFU count method, we found that Triptolide decreased the growth of Mtb HN878. Alamar Blue assay showed that this decreased Mtb HN878 growth was not as a result of direct targeting of Mtb HN878 by Triptolide, but rather evoking MDMs intracellular killing mechanisms which we speculate could include Triptolide-induced enhancement of MDMs effector killing functions mediated by lncRNA-PACER and lincRNA-p21. Altogether, these results provide proof of the modulation of lncRNA-PACER and lincRNA-p21 expression by Triptolide, and a possible link between these lncRNAs, the enhancement of MDMs’ effector killing functions and the intracellular Mtb-killing activities of Triptolide. These findings prompt for further investigation of the precise contribution of these lncRNAs to Triptolide-induced activities in MDMs